Engineering System Resilience to Global Risks: A Resilience Engineering Approach in Modern Infrastructure - Miko Mei Irwanto (Pt. Anagata Sembagi Education, 2026)
Modern infrastructure systems are increasingly exposed to complex and interconnected global risks, including natural disasters, climate change impacts, cyber threats, and cascading systemic failures. Traditional risk management frameworks have proven insufficient to address the dynamic and uncertain nature of these challenges. This study examines the application of resilience engineering principles as a comprehensive framework for strengthening engineering systems against global risks. Through a systematic literature review of 20 peer-reviewed publications spanning 2013–2026, this paper synthesizes current theoretical foundations, methodological approaches, and practical implementations of resilience engineering in modern infrastructure contexts. The findings reveal four core resilience dimensions, absorptive, adaptive, restorative, and transformative capacity that collectively define a system's ability to withstand, respond to, and recover from disruptive events. Key strategies identified include multi-hazard life-cycle assessment frameworks, performance-based resilience metrics, interdependency modeling, and socio-ecological resilience integration. The study also highlights critical research gaps, particularly in quantifying transformative resilience and operationalizing resilience indices for heterogeneous infrastructure networks. This review contributes to the growing body of knowledge on resilience-based infrastructure design and policy, offering actionable recommendations for engineers, urban planners, and policymakers.